Metacognitive Awareness as a Destructive Risk Factor Prevention in Educational Environment - Alla Frolova (ARPHA Proceedings, 2022)
Metacognition as a phenomenon is the subject of discussion in many scientific spheres. In modern reality, a person's efforts to overcome life difficulties is studied within the framework of the cognitive paradigm, where representatives analyze the way the person perceives and assesses their metacognitive capabilities, how the level of cognitive response is related to the coping strategies and self-regulation, in what ways the individual's motivation in overcoming destructive risks can be enhanced (Wells, 2011; Sun et al., 2017).Thus, the study of the features of cognitive-behavioral and metacognitive responses allows us to determine the manifestation of destructive risks in the individual and predict the possibility of maladaptation.Based on the foregoing, the purpose of the study is to identify peculiarities of metacognitive awareness, investigate the relationship of metacognitive involvement in cognitive style activities, study markers, destructive "risk zones" contributing to the formation of maladaptive forms in behavior. Research methods used were as follows: the questionnaire “Metacognitive Awareness Inventory” of Shraw and Dennison adapted by Karpov and Skityaeva (2005); “The Embedded Figures Test” (Witkin et al., 2002). “The Free Associations Methodology” (Gardner et al., 1959) was applied as well to assess cognitive style “rigid-flexible cognitive control”; the questionnaire “Negative prognosis” (Sychev, 2008); the test of anticipatory consistency (predictive competence) (Mendelevich, 2005); the scales of dysfunctional distortions by Beck and Weisman adapted by Zakharova (2013) . It was established that dysfunctional beliefs are imprinted in the individual system of meanings in the form of stable cognitive schemes that cause a negative metacognitive personality style. It was revealed that interrelated indicators of metacognitive involvement, anticipatory consistency, and constructive cognitive style are predictors of effective personal resources.